Volume- and temperature-dependent permeabilities in isolated rat liver cells. - Berthon, B (1980)
1. Water, K, Na and Cl contents and fluxes of K and Na were determined in isolated rat hepatocytes incubated at 1 degrees C (90 min) then at 38 degrees C (60 min). At 1 degrees C cells progressively gained Na and Cl, lost K and increased their volume by 17%. 2. Rewarming triggered a net loss of K and gain of Na. They were transitory (about 60 sec) being overcome rapidly by movements in the opposite direction until cells recovered their initial K and Na gradients. 3. Determination of time courses of the K rate constant (kappa' K) and net Na influx (phi Na) in cells incubated in ouabain K-free media indicated that these paradoxical movements were due to a temporary shunting of the Na pump by sudden increases in K and Na permeabilities. 4. Increases in kappa' K and phi' Na were not sensitive to inhibitors of Ca-activated K channels such as quinine (10(-3) M) of apamin (10(-8) M), suggesting they were not dependent on internal ionized Ca. 5. In control media containing 1.8 mM-Ca divalent ionophore A23187, though stimulating the Ca pump (Ca efflux), presumably by increasing internal ionized Ca concentration, did not cause substantial and rapid changes in K permeability. This supports the hypothesis that Ca-sensitive K channels are lacking in rat hepatocytes. 6. A 10% increase in cell volume provoked by a hypo-osmotic shock triggered increases in both kappa' K and phi' Na with time courses very similar to those brought about by rewarming. 7. It is proposed that transient changes in K and Na permeabilities are the consequence of the cell swelling, induced by cooling. These volume-dependent permeabilities are blocked at 1 degrees C and revealed by rewarming.